pengaruh Konflik Peran, Ambinguitas Peran, Terhadap Kinerja Wanita Berperan Ganda Yang Dimoderasi Oleh Kecerdasan Emosional - Mamesah, Nastasya (JURNAL RISET BISNIS DAN MANAJEMEN, 1996)
This study aims to determine the ability of emotional intelligence in the moderating influence the role of conflict and role ambiguity on the women in dual role. Respondent of this study is 72. The data collection in this study using a questionnaire. Questionnaires were distributed as many as 72 pieces or all women working in PT. Bank Rakyat Indonesia, Tbk Branch Manado, while questionnaires were returned 50 and 48 it can be processed. This study using purposive sampling method and hypotheses are tested using an moderated regression analysis (MRA) with SPSS. The results of this study shows the emotional intelligence is able to moderate the influence of role conflict and role in the performance of and the ambiguities of the women in dual role. Keywords: role conflict, women in dual role, emotional intelligence